2020
DOI: 10.1111/dth.13594
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of skin rash in pediatric patients with COVID ‐19: Three case presentations

Abstract: The authors certify that they have obtained all appropriate patient consent forms. In the form the patient(s) has/have given his/her/their consent for his/her/their images and other clinical information to be reported in the journal. The patients understand that their names and initials will not be published and due efforts will be made to conceal their identity, but anonymity cannot be guaranteed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…Out of that 5 were case series, [16], [17] [18], [19] [20] 4 were case reports, [21], [22] [23], [24] and 4 were original studies. [25], [26] [27], [28] Maximum number of articles were reported from Italy, [16], [19] [20], [21] [22], [24] [26] followed by Spain, [17] [23], [25] France, [8] Turkey, [28] and USA. [27] All studies were published during April &May 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of that 5 were case series, [16], [17] [18], [19] [20] 4 were case reports, [21], [22] [23], [24] and 4 were original studies. [25], [26] [27], [28] Maximum number of articles were reported from Italy, [16], [19] [20], [21] [22], [24] [26] followed by Spain, [17] [23], [25] France, [8] Turkey, [28] and USA. [27] All studies were published during April &May 2020.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 149 different patients were analyzed & discussed. The youngest case is of 8 months female baby (28) and the oldest is an18-year male [19] with the mean patient age at 11.096 years (SD±4.56 years) Males comprised 85 cases (57%) while females accounted for 64 cases (43 %). Acrally located erythematous to violaceous maculopapular lesion having blurred edges, occasionally with super cial bullae and focal hemorrhagic crust was the most common nding in 127 children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous manifestations have been increasingly reported in association with the coronavirus disease 2019 (COVID- 19) pandemic. Despite an increase in relevance, much remains unknown concerning the characterization, incidence, and pathogenesis of these dermatological symptoms.…”
Section: Scope and Significancementioning
confidence: 99%
“…12,13,[15][16][17][18] Despite a large case series from Spain reporting simultaneous onset of many maculopapular lesions with COVID-19's systemic symptoms, 11 other studies had noticed a later onset in their smaller patient populations. [12][13][14]19 Studies with a later onset of cutaneous manifestations reported average latency times of 27.6 days and 27.85 days. 12,13 Mean duration of the exanthems ranged from 8.6 to 11.6 days.…”
Section: Maculopapular/morbilliform Lesionsmentioning
confidence: 99%